Blended Project Based-Instruction and its Impact an High Order Thinking Skills - Pryla Rochmahwati; Issy Yuliasri; Sukarno Sukarno; Dwi Anggani Linggar Barathi (Universitas Negeri Semarang, 2021)
This research is aiming at scrutinizing the effect of blended project-based learning instruction on students’ higher order of thinking skill as well as its effective practice. It employed quasi-experimental research design. The population was the 4th semester pre-service teachers of English Education Department at IAIN Ponorogo. The data were collected through test. The quantitative data were analyzed by ttest using SPSS program for Windows. The finding showed that there is significant effect of blended project-based learning instruction on students’ higher order of thinking skill as it can be seen from the result of ttest is 1.798 which is higher that ttable at 1. 679. The greatest number of pre-service teachers reached out level 3 in Factual domain, however for the conceptual, procedural and metacognitive domain, they reached out level 2 respectively. Finally, the finding is expected to facilitate teachers as well as curriculum planners to integrate blended and project- based learning into accounts while designing EFL instruction.